Karakteristik Mineral Tanah Berbahan Vulkanik dan Potensi Kesuburannya di Pulau Jawa - Setiyo Purwanto; Rachmat Abdul Gani; Sukarman Sukarman (Jurnal Sumberdaya Lahan, 2018)
Abstrak. Pulau Jawa memiliki gunung api terbanyak di Indonesia (45 buah). Material bersumber dari erupsi gunungapi (piroklastik) di sekitar Pulau Jawa menyebabkan kualitas kesuburan tanah di Pulau Jawa lebih baik dibandingkan wilayah lain di Indonesia. Wilayah pegunungan sering dijadikan sebagai daerah sentra usaha pertanian. Kajian terkait karakteristik mineralogi tanah dari bahan vulkanik di Pulau Jawa telah banyak dilakukan, namun terbatas pada penelitian yang bersifat mandiri (perwilayahan pegunungan). Mengungkap dan memperbandingkan data berkait karakteristik mineralogi tanah vulkanik di Pulau Jawa akan memperkaya hasanah keilmuan dan bermanfaat dalam tata kelola lahan pertanian. Abstract. Java Island has the most volcanoes in Indonesia (45 volcanoes). Materials sourced from volcanic eruptions (pyroclastic) around the Java Island have caused the quality of soil fertility in Java is better than other regions in Indonesia. Mountainous areas are often used as a center of agricultural business, especially horticulture. Studies related to the mineralogical characteristics of soil from volcanic material on the Java Island have been widely carried out, but are limited to independent research (single mountain territory). Revealing and comparing data related to the mineralogical characteristics of volcanic soils in the Java Island will enriches scientific knowledge and useful in the management of agricultural land.